Comparative study of preoperative prophylactic antibiotic versus no antibiotic in patients undergoing elective laparoscopic cholecystectomy - Charan Shrestha, Bhupendra; Adhikari, Milan; Timsina, Aliza (Birat Journal of Health Sciences, 2024)
Introduction: Laparoscopic cholecystectomy stands as one of the most commonly performed surgical procedures worldwide, primarily indicated for symptomatic cholelithiasis and associated gallbladder diseases. Despite its minimally invasive nature, concerns persist regarding the risk of postoperative infections, which can significantly impact patient outcomes and healthcare costs. Antibiotic prophylaxis has long been considered a standard practice to mitigate this risk, yet the optimal approach remains a subject of debate. Objective: This research was aimed to elucidate the comparative effectiveness of preoperative prophylactic antibiotic versus no antibiotics in patients undergoing elective laparoscopic cholecystectomy. Methodology: We conducted a prospective comparative study at Birat Medical College Teaching Hospital from 27 November 2023 to 27 February 2024. A total of 200 patients undergoing elective laparoscopic cholecystectomy were enrolled consecutively and assigned to the no antibiotic prophylaxis group and single dose preoperative antibiotic prophylaxis group (SD) on a roll basis. The SD group received a preoperative injection of ceftriaxone (third generation of cephalosporin) (1gm) 30 minutes before the surgical procedure. Data were collected and analyzed using SPSS version 23. Results: The overall rate of SSI was 4% in our study. Five out of 100 patients who received prophylactic and 3 out of 100 patients who did not receive antibiotics developed surgical site infection(SSI). However, the difference was not statistically significant. Conclusion: Our study comparing preoperative prophylactic antibiotics versus no antibiotics in elective laparoscopic cholecystectomy patients reveals no significant association between antibiotic use and outcomes such as surgical site infections and fever.